MOLECULAR CHARACTERIZATION OF RHIZOCTONIA SOLANI AG-7 CAUSING ROOT ROT ON COTTON CROP IN INDIA - MANJU RANI; J. S. RANA; K. K. DAHIYA; VIKAS BENIWAL (International Journal of Pharma and Bio Sciences, 2013)
Rhizoctonia solani (Kuhn) is one of the most important cotton crop pathogens. Rhizoctonia solani anastomosis groups (AGs) 7 and 4 are proven to be the most common pathogenic fungal strains on cotton crop. AG-7 can cause root rot in plants while damping-off of seedlings is most frequently attributed to AG-4. Sequencing of the ITS (Internal Transcribed Spacer) region of ribosomal DNA was performed on northern Indian isolates in order to determine their relatedness. Sequence analysis using BLAST revealed that rDNA ITS region of MV1 [JX576189.1] was at least 98% identical to that of other AG7 isolates (AY154305.1) on the GenBank database. Bio-molecular evaluation by means of electrophoretic profile of isozyme polyglacturonase and RFLPs of ribosomal DNA internal transcribed spacers were carried out. The isolates shared a common pectic zymogram while sequence analysis of rDNA showed a closer similarity to anastomosis group-7(AG-7). Based on morphological characteristics, hyphal fusion compatibility and sequence analysis, 98% of the isolates collected belonged to AG-7 and 2% of the isolates were AG-4 R.solani . This is the first report of R. solani AG-7 infecting cotton crop in Northern India.